FACTORS INFLUENCING THE PREVALENCE OF MALARIA AMONG CHILDREN BELOW 10 YEARS AT NYIMBWA HEALTH CENTER IV, LUWEERO DISTRICT. A CROSS-SECTIONAL STUDY. - KATENDE , SAMUEL; NAMUTEBI , FLORENCE (Student’s Journal of Health Research Africa, 2024)
Background: Broad objective: To assess the factors influencing the prevalence of malaria among children below 10 years at Nyimbwa Health Center IV, Luweero district. Specific objectives: To determine, evaluate, and assess the demographic, economic, and environmental factors that influenced the prevalence of malaria among children below 10 years at Nyimbwa Health Center IV, Luweero district. Methodology: A cross-sectional study in which both qualitative and quantitative data were collected from a sample of 81 respondents who were obtained using a simple random sampling technique, The data collection method was a face-to-face interview using a questionnaire. Results: Malaria cases were children aged between 9 and 10 years( 33%),60% lived in villages, 52% of cases were males and 48% females, 42% were Baganda, (46%) from families earning between UGX 110,000 to 300,000 monthly, 79% from houses constructed with cement, 89% used latrines,52% got water from boreholes,72% lived in homes with nearby stagnant water (72%).85% lived in houses with no holes, 79% reared some animals and 57% disposed of wastes in rubbish pits. Conclusions: The study established that factors like the age and sex of the children, the economic status of the family, presence of stagnant water greatly influenced the prevalence of malaria. Other factors included education levels of guardians, religions, places of residence, source of water for domestic purposes, method of excreta, and waste disposal. Recommendations: Guardians should make sure children sleep under treated mosquito nets, exclusive breastfeeding for at least the first six months and a balanced diet for older children, clearing bushes and draining stagnant water near homes to keep away from breeding mosquitoes. Health workers should create awareness of malaria prevention and effective treatment of positive cases. The government should equip health facilities with adequate staff, drugs, and necessary equipment, and timely delivery of free mosquito nets to the population.